S115 NADPH Oxidase 4 Over-Expression Mediates Epithelial Ciliary Dysfunction in Neutrophilic Asthma. (19th November 2012) - Wan, WYH; Woodman, L; Hirst, R; Haldar, K; Gomez, E; Sutcliffe, A; Desai, D; Barer, M; O'Callaghan, C; Brightling, C
Abstract : Objective: Epithelial ciliary dysfunction is a feature of asthma and contributes to persistent symptoms and recurrent exacerbations. We sought to examine whether its cause is due to an altered airway environment or an intrinsic abnormality. Methods: Primary epithelial cells were obtained from 46 subjects with asthma and 28 healthy controls for culture. Air-Liquid-Interface (ALI) cultures fully differentiated from human primary airway epithelial cells were stimulated with asthmatic sputum, with or without the presence of antibiotics. Ciliary function was assessed using video-microscopy. Bacterial 16S load in sputum and ALI culture before and after addition of sputum were assessed by qPCR. Oxidative stress was enumerated by 8-oxo-dG expression in bronchial biopsies using immunohistochemiatry in 27 asthmatics and 9 healthy controls, and in basal epithelial cells following hydrogen peroxide (H2O2) stimulation assessed by the DCFDA assay. NADPH oxidase (NOX) subtype 4 mRNA expression was quantified using qPCR. The effect of NOX4 inhibition, using GKT137831, on ciliary dysfunction was evaluated using fresh epithelial strips from 13 asthmatics. Results: In ex vivo ciliated epithelial ALI cultures ciliary dysfunction did not persist, but was evident in cells from asthmatics following exposure to sputum. Bacterial load increased in the epithelial cultures following exposure to sputum, but were not different between health and disease suggesting that both exposure to an asthmatic environment and a susceptibility to stress is necessary to induce ciliary dysfunction in asthma. In vivo the oxidative stress burden in the bronchial epithelium was heightened and related to airflow obstruction and neutrophilic inflammation. NOX4 mRNA expression was significantly elevated in epithelial cells from neutrophilic asthmatics, and H2O2-induced intracellular reactive oxygen species generation was increased compared to health and attenuated by NOX4 inhibition. Critically, in fresh epithelial cells from asthmatics inhibiting NOX4 markedly improved ciliary function and was related to the intensity of neutrophilic inflammation. Conclusions: These data suggest that in asthma NOX4 up-regulation promotes the susceptibility of the bronchial epithelium to develop ciliary dysfunction in the presence of an abnormal microenvironment. NOX4 inhibition attenuates ciliary dysfunction. This implicates NOX4 as a potential therapeutic target for asthma, particularly in those with neutrophilic predominant disease.